Comparison of Mean Duration of Drain Removal in Quilting VS Non Quilting Wound Closure in Modified Radical Mastectomy (Medical Forum Monthly, 2024)
Objective: To compare mean time for drain removal with quilting and non-quilting wound closure techniques in modified radical mastectomy.Study Design: Single-centered prospective randomized control studyPlace and Duration of Study: This study was conducted at the Department of General Surgery, Liaquat National Hospital, Karachi Study duration lasted for 1 year from April 2016 to March 2017.Materials and Methods: All patients who had a Modified radical mastectomy during this period were included in this study. Total 72 patients were included. 36 Patients were enrolled either in Group-A (quilting) or in Group-B (no quilting). Quilting was done in group-A. 2 Radevuac drains (flap drain & axillary drain) were placed in both groups. drains were removed when total drain output was 20cc or less per day. Final outcome was measured in term of total days of drain removal. Descriptive statistics were calculated. Stratification was done. Post stratification t test was applied. P-value ≤0.05 was considered as significant.Results: Mean duration of flap drain removal in group-A was 8.52±5.15 days and 10.41±4.23 days in group-B. Mean duration of axillary drain removal in group-A was 12.91±5.54 days and 17.55±7.19 days in group-B. Mean total duration of drain removal was 14.63±5.09 days in group-A and 18.38±6.36 days in group-B. This mean difference of total duration of drain removal was found significant.Conclusion: Quilting is an efficient method to significantly reduce the duration and volume of wound drainage.